The video analysis as teaching tool in archery youth - Napolitano, S.; Tursi, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The aim is to evaluate the effects of motor imagery practice in training. The motor imagery is a cognitive process of mental simulation of actions in absence of movement. There are two methods to improve skills learning through motor imagery: in first person and In third person. The biological basis on which the motor imagery theory is founded, is formed by: mirror neurons. The archery is a typically closed skill sport. It is a `closed skill` sport characterized by repetition, as precise as possible, of a movement already known automated. Method: It is an experimental approach and it consists of two steps. Both groups were video taped in the execution of sport skills and evaluated, through a check list made by archery indicators: positioning phase, traction and aim, release and follow through in 4 level of descriptors by technicians every four months. A sample of archery team of children ( 9-11 years old) splitting in control and experimental groups, after a pre-assessment, performed by technicians, about technical skills through an evaluation grid prepared `ad hoc` on technical fundamentals taken into the study to form two homogeneous groups (Experimental group n = 10, control group n = 10). Experimental group using modelling video performed by a athletes of National Italian Archery Team could lead to significant changes in technical skills. The results are based on the neuro-scientific assumption on the activity of mirror neurons that allow you to use the same nervous substrate for actions performed or observed, or thinked. Result: Data recruit at starting, ongoing and final training program and their analysis, evaluation and comparison by control group show percentage of 9% better outcomes. particularly, at final training shows a minimum improvement 3.2% than ongoing phase that gives a maximum improvement 9.6%, while a substantial balance in the control group with a medium improvement of 3.2% in every phase of training program. Conclusion: In this study two basic aspects of the performance are examined: the motor execution and the motor imagine. Both share the same neuro-motor mechanism: the motor imagery. Using video analysis by modelling approach as a tool in teaching method has the maximum improvement in first part of training program according to motor control theory of Motor Imagery. Starting phase should be played by video modelling teaching method to learn sport skills in qualitative aspects and then should be played according good sport practice in didactics.